Multi-scenario Prediction of Carbon stock in the Loess Plateau Based on Coupled PLUS-InVEST-Geodetector Model - He, Zhichen; Zhang, Lele; Liu, Rui; Li, Yanzhi; Zhang, Yuxin; Jiang, Jiaqi (Transactions on Environment, Energy and Earth Sciences, 2024)
Since the Loess Plateau is a typical ecologically fragile area in China, it is crucial to investigate how land use/land cover and carbon stock change under various scenarios and the factors that influence these changes for the region's ecological protection and sustainable development. In this study, we coupled the PLUS-InVSET-Geodetector model to predict the land use and carbon stock of the Loess Plateau in 2040 based on four scenarios: natural development, ecological protection, water conservation, and economic development. We also examined the effects of various driving factors on the LUCC (land use/cover change) and carbon stock. The results show that the carbon stock in the Loess Plateau will increase under all four scenarios from 2020 to 2040, with the best sequestration effect under the natural development scenario, in which the carbon stock will increase by 1.9% compared with that in 2020; the spatial distribution pattern of carbon stock in the Loess Plateau will remain unchanged from 2000 to 2040, and the main influences of these factors are NDVI, precipitation and slope. According to the requirements of the “dual carbon” target, based on the prediction results, the best option for the Loess Plateau's future development is the natural development scenario.